Decreases in relative humidity across Australia. (1st July 2021) - Denson, Eleanor; Wasko, Conrad; Peel, Murray C
Abstract: How relative humidity is changing is important for our understanding of future changes in precipitation and evaporation. For example, decreases in relative humidity have the potential to increase evaporation and evapotranspiration increasing water scarcity. Since projected precipitation changes are highly uncertain, there is significant research relating precipitation changes to more certain local temperature increases, but such research often assumes relative humidity will remain constant. Here, we investigate how absolute and relative humidity across Australia have changed over 1955–2020. Absolute humidity, measured by dew point temperature, has remained relatively constant, while relative humidity has decreased on average over land by approximately −1%/decade. This suggests that assuming constant relative humidity when predicting future extreme precipitation using temperature or absolute humidity associations may result in over-estimation of future extreme precipitation intensities. As absolute humidity, measured by dew point temperature, was found to be relatively constant, we conclude the decrease in relative humidity is not due to a lack of water available for evaporation but may instead be the result of evaporation not increasing in line with temperature increases.